The Cost of Tuberculosis Care: Assessing the Economics of Tuberculosis for Patients and the Health Care System - D'Silva, Olivia (Université d'Ottawa / University of Ottawa, 2023)
Background: Tuberculosis (TB) is a major global health threat that results not only in health consequences but also economic consequences. Since 2015 the World Health Organization (WHO) has developed a strategy with the aim of ending the global burden of TB by reducing TB-related deaths, reducing TB incidence, and eliminating the burden of TB-related catastrophic costs for patients and their families. In order to reach these targets, we need to implement effective TB diagnostic and care strategies that are feasible for both patients as well as the health care system. -- Methods: This study consists of two manuscripts which assess the economic burden of TB - one from the patient perspective and the other from the health system perspective. The first manuscript is a systematic review aimed to determine the costs incurred by patients and their households while receiving TB care with direct (medical and non-medical) as well as indirect costs being examined for the pre-diagnostic, post-diagnostic and total phase of care. It analyzed studies with varying patient populations from low-, middle-, and high-income settings to help estimate key factors that drive patient costs. Furthermore, it assessed the proportion of patients that incurred catastrophic costs and the coping strategies that they resorted to in order to offset the costs of TB care. The second manuscript is a modelling study which aimed to develop, parameterize and analyze a decision analytic model to determine the cost, health outcomes as measured by disability-adjusted life years (DALYs) averted and the cost-effectiveness of second-generation lateral flow lipoarabinomannan assay (SG LF-LAM) diagnostic algorithms in people living with HIV (PLHIV) per DALY averted. This model examined four different strategies - 1) the standard of care (SOC) Gene Xpert MTB/RIF only, 2) Gene Xpert MTB/RIF plus LF-LAM for all patients, 3) Gene Xpert MTB/RIF plus LF-LAM for patients with a negative Xpert result, and 4) Gene Xpert MTB/RIF plus LF-LAM for patients who are symptom negative. -- Results: A systematic review showed that total patient costs related to TB care ranged from a mean of $2.80 to $19,153.80 (2019 USD) with costs largely dependent on geographic location as well as patient population, Direct medical and indirect cost components were the largest source of costs for patients and their families while receiving TB care. Direct medical costs included the cost of medication, consultations, diagnostics, follow-up testing, and hospitalization while indirect costs mainly consisted of loss of income. The costs of TB care were considered catastrophic for the majority of patients resulting in them using coping strategies to offset the burden of costs. In the second manuscript, the cost-effectiveness analysis Xpert only was found to be dominated by Xpert + FujiLAM conditional on a negative Xpert with an ICER of 1,000 USD/per DALY averted compared to the standard of care (SOC) Xpert only. Sensitivity analysis found that variations in the key model parameters had an impact on the cost and effectiveness calculations obtained through the model. -- Conclusions: The burden of TB-related costs impact both patients and the health care system at all stages of TB care. Novel diagnostic strategies like the inclusion of FujiLAM for TB diagnosis in PLHIV are cost-effective tools that can aid in case detection and reduce severe outcomes of TB. In order to reduce the TB burden and achieve the "End TB" strategy goals, studies need to work to understand the key components involved in these costs as well as work to develop and implement effective, feasible interventions for TB diagnostics and care.
Keywords: Tuberculosis; Health Economics; Patient Costs; Catastrophic Costs; Human Immunodeficiency Virus; FujiLAM; LF-LAM; Cost-Effectiveness; Gene Xpert MTB/RIF